Mycorrhiza - Mycorrhiza (Springer Nature, 2026)
Mycorrhiza is an international journal devoted to excellent research into mycorrhizas - the widest symbioses in nature, involving most plants and diverse soil fungi world-wide. Articles cover topics ranging from molecule to ecosystem, through cell and plant, from fundamental to applied science. We only publish papers that advance understanding of mycorrhizal plants and fungi.
FI 1
Q2
Keywords: Agriculture; Aquaculture & Food Science; Soil; Agricultura; Acuacultura; Edafología; Micorrizas; Acuerdos transformativos; Transformative agreements; Agroecología; Silvicultura; Biodiversidad; Cambio global